2007
DOI: 10.1136/jcp.2006.046201
|View full text |Cite
|
Sign up to set email alerts
|

Calcification in breast lesions: pathologists’ perspective

Abstract: Evaluation of calcification in breast lesions is a major assessment criterion for breast mammography. The morphology and distribution of the calcification are related to the histology of the lesions. Radiologically, calcifications can be divided into: benign; intermediate concern; and higher probability of malignancy according to the morphology. Different pathological entities may give rise to different calcifications. Fibrocystic changes may give rise to milk of calcium or teacup type calcification, or small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 40 publications
3
53
2
4
Order By: Relevance
“…Similar to what we observed in the dog, the incidence of calcification in human DCIS ranges between 42% and 72% (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Up to 90% of DCIS lesions in human are detected on the basis of mammograpically visible microcalcifications (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). All canine DCISs were associated with comedo-type carcinoma and contained microcalcification and, interestingly, were mammographically detected.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar to what we observed in the dog, the incidence of calcification in human DCIS ranges between 42% and 72% (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Up to 90% of DCIS lesions in human are detected on the basis of mammograpically visible microcalcifications (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). All canine DCISs were associated with comedo-type carcinoma and contained microcalcification and, interestingly, were mammographically detected.…”
Section: Discussionsupporting
confidence: 68%
“…Typical benign calcifications in human are similar to that we have seen in the dog and are large, smooth, popcorn-like, round, dense, and scattered over a large area. These lesions in human do not need further investigations or close follow-up (26,34). About 47% of malignant tumors in this study showed microcalcification.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The presence of microcalcifications indicating HER2 overexpression could be explained by the fact that DCIS, which may be a component of invasive cancer, is frequently HER2-positive and often shows microcalcifications (108)(109)(110). Alternatively, poorly differentiated tumors more often show central necrosis and rapid growth, resulting in deposition of microcalcifications along the ductal structures, and the finding could thus also be a reflection of the more aggressive nature of HER2-positive invasive cancers (109). Correlation between the presence of a mass (significant on ultrasound but also corroborated by the mammography and MRI findings) and decreased chance of HER2 overexpression is also likely a reflection of DCIS (less often presenting as a mass and more frequently HER2-positive; ref.…”
Section: Discussionmentioning
confidence: 99%
“…The size of each contrast element is 25 mm 2 , which is in the range of sizes for calcifications of fibroadenoma and fat necrosis. 34 Iodine is relevant for contrast-enhanced imaging to detect angiogenesis in tumors. 24 Although the size of tumors and calcifications that indicate malignancy can be smaller than 25 mm 2 , the focus of this investigation is on the initial test of the theory and its performance given the chosen attenuation functions.…”
Section: Iic Measurement Phantomsmentioning
confidence: 99%